2015
DOI: 10.1136/injuryprev-2015-041583
|View full text |Cite
|
Sign up to set email alerts
|

Cause, nature and care-seeking behaviour for injuries among community-dwelling older adults, USA, 2004–2013

Abstract: Our results suggest that injuries, especially falls, are a pressing public health concern for the growing population of older adults. Injury prevention outreach should take extra measures to reach certain subgroups of older adults that have been identified as especially vulnerable. Because so many injuries are due to reasons other than falling and/or do not result in hospitalisation, more interventions should be designed for general injury prevention and outpatient settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 23 publications
(19 reference statements)
0
11
0
Order By: Relevance
“…A much higher proportion of American elders lived alone than their Chinese counterparts (30% vs 10%), while a much higher proportion of Chinese elders lived with others with no spouse or partner present than their American counterparts (17% vs 11%). In the USA, coresidence of older adults with others may indicate vulnerable health and need for live-in assistance 20. We found that American elders living with others with no spouse or partner present reported worse health status than those in other living arrangements.…”
Section: Discussionmentioning
confidence: 67%
“…A much higher proportion of American elders lived alone than their Chinese counterparts (30% vs 10%), while a much higher proportion of Chinese elders lived with others with no spouse or partner present than their American counterparts (17% vs 11%). In the USA, coresidence of older adults with others may indicate vulnerable health and need for live-in assistance 20. We found that American elders living with others with no spouse or partner present reported worse health status than those in other living arrangements.…”
Section: Discussionmentioning
confidence: 67%
“…Moreover, approximately 30% of people over 65 years of age living in the community fall each year, according to a review based on the Cochrane database [ 1 ]. Injuries sustained in a fall were more likely to be serious than those due to other reasons in community-dwelling older adults that were characterized as hip fracture, head injury and/or other fracture [ 2 ]. From viewpoints of prevention medicine, all trials to reduce rate of falling or consequence of falling would be worthy.…”
Section: Introductionmentioning
confidence: 99%
“…The toolkit includes a questionnaire and algorithm (Figure 1) that guides clinicians through screening and assessment for risk factors to enable classification of an older adult as low, moderate, or high risk for falling and recommends referrals and interventions to address individually identified risk factors (Stevens & Phelan, 2013). Successful interventions for fall prevention include, but are not limited to, participation in programs to encourage exercise to maintain and increase strength and balance, medication management, and home modifications (Xu & Drew, 2017). Screening for fall risk and addressing modifiable risk factors may potentially decrease falls by as much as 25% (Houry, Florence, Baldwin, Stevens, & McClure, 2016).…”
Section: Introductionmentioning
confidence: 99%